Metabolites extracted from microorganisms as potential inhibitors of glycosidases (α-glucosidase and α-amylase): A review - Wang, Xiaojing; Li, Jiaying; Shang, Jiaqi; Bai, Jing; Wu, Kai; Liu, Jing; Yang, Zhijun; Ou, Hao; Shao, Lei (Frontiers in Microbiology, 2022)
α-Glucosidase and α-amylase are the two main glycosidases that participate in the metabolism of carbohydrates. Inhibitors of these two enzymes are considered an important medical treatment for carbohydrate uptake disorders, such as diabetes and obesity. Microbes are an important source of constituents that have the potential to inhibit glycosidases and can be used as sources of new drugs and dietary supplements. For example, the α-glucosidase inhibitor acarbose, isolated from Actinoplanes sp., has played an important role in adequately controlling type 2 diabetes, but this class of marketed drugs has many drawbacks, such as poor compliance with treatment and expense. This demonstrates the need for new microorganism-derived resources, as well as novel classes of drugs with better compliance, socioeconomic benefits, and safety. This review introduces the literature on microbial sources of α-glucosidase and α-amylase inhibitors, with a focus on endophytes and marine microorganisms, over the most recent 5 years. This paper also reviews the application of glycosidase inhibitors as drugs and dietary supplements. These studies will contribute to the future development of new microorganism-derived glycosidase inhibitors.